Comparison of Serum Trace Nutrient Concentrations in Epileptics Compared to Healthy Dogs - Vitale, Samantha; Hague, Devon Wallis; Foss, Kari; de Godoy, Maria Cattai; Selmic, Laura E. (Frontiers in Veterinary Science, 2019)
Idiopathic epilepsy (IE) is a common cause of seizures in dogs. There are several investigations regarding serum concentrations of trace nutrients, including copper, selenium, zinc, manganese, and iron in human epileptics and animal models. However, research of this nature in dogs with epilepsy is lacking. The purpose of this prospective study was to compare serum concentrations of several trace nutrients in healthy dogs to dogs with idiopathic epilepsy. Healthy client-owned dogs (n=50) and dogs with IE (n=92) were enrolled and blood samples were collected for trace nutrient analysis. Epileptics were subdivided into three groups: controlled: n=27, uncontrolled: n=42, and untreated: n=23. Serum was evaluated for concentrations of copper, selenium, zinc, cobalt, manganese, molybdenum, and iron using inductively coupled plasma mass spectroscopy. Uncontrolled epileptics had significantly higher manganese concentrations compared to normal dogs (p=0.007). Untreated epileptics had higher iron levels than the other three groups (p=0.04). Significantly higher levels of copper (p<0.0001) were found in controlled and uncontrolled epileptics compared to normal or untreated dogs. Significantly higher levels of molybdenum (p=0.01) were found in controlled epileptics compared to normal or untreated epileptics. Uncontrolled and controlled epileptics had significantly higher levels of selenium (p=0.0003) versus normal dogs, and uncontrolled epileptics had higher levels of zinc (p=0.0002) than normal and untreated dogs. The significant difference in serum concentrations of several trace nutrients (manganese, selenium, and zinc) may suggest a role for these nutrients in the pathophysiology and/or treatment of epilepsy. Additionally, these results suggest that anti-convulsant therapy may affect copper and molybdenum metabolism.